PENGARUH BIMBINGAN KELOMPOK TERHADAP KEPEDULIAN SISWA PADA LINGKUNGAN SEKOLAH ADIWIYATA DI SMA NEGERI 5 PEKANBARU - Retnowaty Wulyadi; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Environmental education creates characters of environmental caring which will be have by somebody to repair and to manage the environment and beneficial without damage the real condition, to maintain and to preserve the environment so that there will be continuous benefits. The effort to foster the character of the students’ environmental awareness was in line with the Adiwiyata’s program. The purpose of this study is to know the levels of students’ awareness before and after group counseling, to know the difference in awareness levels and to know the effect of group counseling to students’ environmental awareness with the Adiwiyata’s school. The research was conducted to the first grade of SMAN 5 Pekanbaru. This research was pre-experimental research with one group pre-test and post-test. The data collection a technique was used questionnaires. The Percentages, Wilcoxon signed-rank test, and Spearman’s rank were used to analyzing the data. The sample was 20 students. The result of this research showed that there were differences in the levels of students’ environmentall awareness before and after and there was a significant improves the group counseling in environment of Adiwiyata School.Keywords: Students’ Awareness, Adiwiyata’s School Environment, Group Counseling